Hot and Cold: Coexistent Graves’ and Hashimoto’s Thyroiditis: A Case Series - Luthfiyya Syafiqa Tahany; I Made Wisnu Wardhana; Darma Irawan (The International Journal of Medical Science and Health Research, 2024)
Introduction: Autoimmune Thyroid Disease (AITD) is a common endocrine disorder, with Graves’ Disease (GD) and Hashimoto’s Thyroiditis (HT) as its primary manifestations. Both conditions share overlapping pathophysiological mechanisms, often leading to diagnostic challenges. This case series aims to describe and analyze cases of hyperthyroidism with complex clinical and laboratory features, suggesting GD, HT, or both. Case Reports: Three patients (Mr. D, 42 years old; Mr. RKA, 47 years old; Ms. MMR, 26 years old) presented with clinical manifestations of hyperthyroidism. Laboratory examinations consistently showed low or very low TSH levels, along with increased Free T3 (FT3) and Free T4 (FT4) levels. A significant finding in all three cases was positive TSH Receptor Antibodies (TRAb), typical for GD, accompanied by very high Anti-Thyroid Peroxidase (Anti-TPO) levels, characteristic of HT. This indicates the possibility of a dual autoimmune process. Discussion: The simultaneous findings of positive TRAb and very high Anti-TPO in all three patients support the concept that GD and HT exist within a single spectrum of AITD and can coexist. The term "Hot and Cold" in the title reflects the dynamics between the hyperthyroid ("hot") phase, caused by TRAb stimulation in GD or Hashitoxicosis, and the potential transition to hypothyroidism ("cold") due to glandular damage by the Hashimoto autoimmune process. These cases highlight the diagnostic complexity, where dominant hyperthyroidism manifestations due to GD coexist with markers of chronic thyroid destruction from HT. Therapeutic implications include administering antithyroid drugs to control hyperthyroidism and the necessity of long-term monitoring to anticipate changes in thyroid function. Conclusion: This case series illustrates the diagnostic and management complexity in AITD patients with overlapping features of GD and HT. The concomitant presence of positive TRAb and very high Anti-TPO underscores the spectrum nature of AITD. Understanding this variability is crucial for clinicians for accurate diagnosis, personalized management, and effective long-term monitoring.